Unlocking Microbial Potential: Innovations in Natural Product Biosynthesis and Therapeutic Applications - Nidhul C S; Navaneeth Gopal (International Journal of Fungi, 2025)
MNPs play a pivotal role in diverse fields, spanning medicine, agriculture, and industry. This review paper synthesizes insights from various discussions on microbial natural products, encompassing their sources, bioactive properties, and applications. We explore microbial diversity contributing to natural product synthesis, emphasizing bacteria and fungi as prolific producers. The methods for isolating and characterizing these compounds underscore the interdisciplinary nature of microbial natural product research utilizing various analytical techniques contributing to the structural characterization and dereplication of microbial natural products and enhancing drug discovery processes. Discussions on the potential therapeutic applications reveal antimicrobial, anticancer, and immunomodulatory properties, highlighting the pharmaceutical relevance of these compounds. Additionally, the agricultural and industrial significance of microbial natural products is explored, showcasing their role as biopesticides, biofertilizers, and enzymes in various processes. The importance of databases like NPA and NPBS in advancing MNP research and the complexities of intellectual property and commercialization in the context of patents and licensing are also discussed. The challenges associated with discovering and harnessing microbial natural products, including issues of cultivation and optimization, are also addressed. This abstract provides a comprehensive overview of the multifaceted aspects of microbial natural products, underscoring their significance in scientific, medical, and industrial domains.
Keywords: Antimicrobial Agents; Microbial Natural Products (MNPs); Structural Characterization; biosynthesis; databases